Role of host genetics and cytokines in Leishmania infection - Krayem, Imtissal; Lipoldová, Marie (Cytokine, 2021)
Cytokines and chemokines are important regulators of innate and specific responses in leishmaniasis, a disease that currently affects 12 million people. We overviewed the current information about influences of genetically engineered mouse models of cytokine and chemokine on leishmaniasis. We found that genetic background of the host, parasite species and sub-strain, as well as experimental design often modify effects of genetically engineered cytokine genes. Next we analyzed genes and QTLs (quantitative trait loci) that control response to Leishmania species in mouse in order to establish relationship between genetic control of cytokine expression and organ pathology. These studies revealed a network-like complexity of the combined effects of the multiple functionally diverse QTLs and their individual specificity. Genetic control of organ pathology and systemic immune response overlap only partially. Some QTLs control both organ pathology and systemic immune response, but the effects of genes and loci with the strongest impact on disease are cytokine-independent, whereas several loci modify cytokines levels in serum without influencing organ pathology. Understanding this genetic control might be important in development of vaccines designed to stimulate certain cytokine spectrum.
Keywords: cytokiny; Leishmania; Leishmaniasis; Cytokines; leishmanióza; Chemokines; Animals; Integrative network; lidé; Genetic control; Host-Parasite Interactions; Humans; zvířata; interakce hostitele a parazita